Efficacy and motor complications of original and generic levodopa in Parkinson's disease treatment - Kasemsap N (Dove Medical Press, 2016)
Narongrit Kasemsap,1 Satrirat Onsanit,2 Piyawan Chiewthanakul,3 Kannikar Kongbunkiat,1 Chonthicha Tanking,1 Nisa Vorasoot,1 Kittisak Sawanyawisuth,1,4 Somsak Tiamkao1,5 1Department of Medicine, Faculty of Medicine, Khon Kaen University, Khon Kaen, 2Department of Medicine, Udonthani Hospital, Udonthani, 3Department of Medicine, Khon Kaen Hospital, 4Research Center in Back, Neck, Other Joint Pain and Human Performance (BNOJPH), 5Neuroscience Research and Development Group (NRDG), Khon Kaen University, Khon Kaen, Thailand Background: In general, a generic drug is considered interchangeable with the original formulated drug. In Parkinson’s disease (PD), generic drug use remains debated. This study was aimed to investigate whether the generic drug was as effective as the original in improving the symptoms of PD and the prevalence of motor complications.Methods: This study was a multicenter cohort study of patients with PD enrolled from three northeast hospitals in Thailand between February 2013 and February 2014. The patients were categorized into original and generic levodopa groups. The clinical characteristics, efficacy, and motor complications were compared between the groups.Results: There were 400 eligible patients. Of these, 327 patients (81.75%) met the study criteria and were classified as the original levodopa group (200 patients, 61.16%) and the generic levodopa group (127 patients, 38.84%). The average age of all patients with PD was 65 years. The duration of PD and the modified Hoehn–Yahr stages were not different between the groups. The total doses of original and generic levodopa-equivalent doses were significantly different (199.97±127.08 versus 305.58±138.27 mg; P-value <0.001) and the actual doses were 198.10±117.92 versus 308.85±139.40 mg (P-value <0.001). Approximately 80% of patients with PD in both groups had good responses (P-value >0.999), but the development of motor complications was significantly greater in the original than in the generic group.Conclusion: Generic levodopa was effective in improving the symptoms of PD. The prevalence of motor complications in the original compound group, at a lower dose of levodopa equivalent, was higher than in the generic group. Keywords: Parkinson’s disease, original, generic, levodopa, efficacy, motor complication